2016
DOI: 10.1002/sys.21320
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach for Developing Decision Aids: From Cognitive Work Analysis to Prototype Design and Development

Abstract: Cognitive Work Analysis (CWA) has proved successful in supporting Human Factors analysis, providing a system‐level view of operations that can be used to understand how systems achieve their missions. However, a critical gap exists in the transition from CWA to prototype design and implementation. The aim of this paper is to fill this gap between CWA and implementation. This paper describes an approach for the design of software system in which CWA descriptions are converted to Unified Modeling Language (UML) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This process is realized through decomposing the interactions obtained from the decision wheel to events and information clues. By comparing the results of task network characteristics analysis under different levels of automation, the feasibility of CWA to quantitative analysis was verified, which was proposed by many studies that showed that the results of human factors engineering analysis should be combined with the quantitative analysis path [50][51][52]. At the same time, this paper is an attempt to extend the application of a formative method.…”
Section: Discussionmentioning
confidence: 86%
“…This process is realized through decomposing the interactions obtained from the decision wheel to events and information clues. By comparing the results of task network characteristics analysis under different levels of automation, the feasibility of CWA to quantitative analysis was verified, which was proposed by many studies that showed that the results of human factors engineering analysis should be combined with the quantitative analysis path [50][51][52]. At the same time, this paper is an attempt to extend the application of a formative method.…”
Section: Discussionmentioning
confidence: 86%
“…The root cause method (RCM) follows the problem to its source [37,38]. RCM assumes that systems and events are dependent and may be related.…”
Section: The Root Cause Methodsmentioning
confidence: 99%
“…Root cause methods and analyses track a problem to its source [37]. This technique is used to find an answer to a question as to what triggered a specific event.…”
Section: Root Cause Analysis (Rca)mentioning
confidence: 99%